2015
DOI: 10.1038/ejcn.2014.266
|View full text |Cite
|
Sign up to set email alerts
|

Dietary whey protein influences plasma satiety-related hormones and plasma amino acids in normal-weight adult women

Abstract: Increased plasma concentrations of some gastrointestinal hormones related to satiety, particularly PP, and of amino acids and their metabolites, may have acted either singly or together to mediate the observed satiety response to whey protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 47 publications
2
40
4
Order By: Relevance
“…In contrast to reports on the lack of food intake inhibition by lactoferrin in humans (50) and mice (20, 51), but consistent with our recent reports (12, 22), we now show that lactoferrin‐enriched diets induced greater hypophagia than comparable isonitrogenous diets. Consumption of high‐protein diets has often been associated with increased circulating concentrations of gut satiety hormones, especially PYY in both humans (28, 29, 38, 47, 48) and rodents (38); however, less is known about the effects of protein quality on PYY‐mediated satiety. Circulating PYY concentrations did not differ in human participants who were fed whey, casein, or pea protein‐enriched diets (3, 4), nor in rats that were fed whey or soy protein for 10 wk (6), whereas PYY mRNA was decreased in the colon of rats after 40 wk of whey protein feeding compared with casein feeding (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to reports on the lack of food intake inhibition by lactoferrin in humans (50) and mice (20, 51), but consistent with our recent reports (12, 22), we now show that lactoferrin‐enriched diets induced greater hypophagia than comparable isonitrogenous diets. Consumption of high‐protein diets has often been associated with increased circulating concentrations of gut satiety hormones, especially PYY in both humans (28, 29, 38, 47, 48) and rodents (38); however, less is known about the effects of protein quality on PYY‐mediated satiety. Circulating PYY concentrations did not differ in human participants who were fed whey, casein, or pea protein‐enriched diets (3, 4), nor in rats that were fed whey or soy protein for 10 wk (6), whereas PYY mRNA was decreased in the colon of rats after 40 wk of whey protein feeding compared with casein feeding (52).…”
Section: Discussionmentioning
confidence: 99%
“…PYY is synthesized and secreted primarily from the enteroendocrine cells of the distal intestines, with protein being a potent stimulus for their secretion in rats (24). Whey protein was found to be more satiating than casein (25,26) and to increase plasma concentrations of PYY in normal participants (3,(26)(27)(28)(29) and in some (30), but not all, rodent studies (4,6,10); however, others reported a dissociation of protein-induced satiety from circulating PYY concentrations (3,31). Thus, despite reports of dietary proteins being potent PYY secretagogues, there is no direct evidence to support the concept that PYY acts as an endocrine signal to mediate the hypophagic effects of such diets.…”
mentioning
confidence: 99%
“…Participants consumed either 500 ml of skimmed milk or yoghurt in random order and intestinal samples were collected over 4 h. On another three test days, blood samples were collected over 8 h following the consumption of 500 ml water, skimmed milk or yoghurt. After milk or yoghurt ingestion, many peptides derived from casein, including α-, β-and κ-caseins, were detected in the stomach, smaller peptides were detected in the duodenum and two long peptides, the κ-caseinoglycopeptide (cCGP) f (106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117) and the N-terminal peptide f(1-23) of α s1 -casein were detected in the plasma. Moreover, cCGP was present for 8 h in the plasma after both milk or yoghurt ingestion.…”
Section: Milk Protein-derived Peptides Identified In the Gastrointestmentioning
confidence: 99%
“…Increasing evidence indicates that milk-derived proteins can alter postprandial incretin hormone responses in healthy, lean, overweight/obese and T2D individuals (19,25,28,89,90,(100)(101)(102)(103)(104)(105)(106) . The majority of evidence points to an enhanced GIP response to intact whey protein (19,25,28,89,100,102) , although there is some disparity in findings (107,108) .…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation